What are the health implications associated with the consumption of energy drinks? A systematic review. (29th January 2013) - Burrows, Tracy; Pursey, Kirrilly; Neve, Melinda; Stanwell, Peter
<x xml:space="preserve">Abstract</x> There is increasing interest regarding the potential health effects of energy drink (ED) consumption. The aim of the present review was to investigate the existing evidence on health outcomes associated with ED consumption. Studies published between 1966 and February 2011 were retrieved and included if they met the following criteria: were randomized or pseudo randomized control trials; studied a human population; reported a health‐related measure; and investigated a whole ED (as opposed to individual ingredients). Study quality was evaluated and data extracted using standardized tools. Fifteen studies were identified, the majority of which had less than 30 participants and included a short term of follow‐up (range: 30 min–3 h). The following outcome measures were included: cardiorespiratory effects, physiological measures, pathological measures, and body composition. The mean dosage of ED was 390 mL (range: 250–750 mL). Commercial ED funding and/or study associations were identified in six studies. Studies investigating long‐term consumption and follow‐up were lacking. The findings from this review do not allow definitive dietary recommendations to be made regarding safe levels of ED consumption; caution should be exercised when consuming these drinks until further high‐quality research is undertaken to substantiate findings.